New species of Floresorchestia from Micronesia living in unusual habitats (Crustacea, Amphipoda, Talitridae) - Lowry, J. K.; Myers, A. A. (Zootaxa, 2013)
The first freshwater talitrid, Floresorchestia pohnpei sp. nov., is described from the island of Pohnpei, Micronesia. Floresorchestia palau sp. nov. is described from supralittoral and shallow-water marine habitats in Palau, Micronesia.